1987
DOI: 10.1007/bf01966527
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of cyclooxygenase and lipoxygenase products by 15-prostaglandin dehydrogenase from human HL-60 leukemia cells

Abstract: A number of prostaglandins and mono-hydroxylated fatty acids were investigated as substrates for NAD-dependent 15-prostaglandin dehydrogenase (15-PGDH) obtained from human HL-60 cells. Lipoxygenase and cyclooxygenase-derived substrates possessing an w-6 hydroxyl moiety (15-HETE, 13-HODD and HHT) were metabolized to corresponding keto derivatives at a rate comparable to that for prostaglandins E2 and F2 alpha. 12-HETE was a poor substrate and 5-HETE was not metabolized. The w-6 hydroxy fatty acids inhibited the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 5 publications
2
5
1
Order By: Relevance
“…We have also demonstrated that differentiated HL-60 cells have about 2-3 times more lysophospholipase activity than do undifferentiated cells. The results shown in Table 1 are similar to results obtained by previous investigators [3][4][5][6][7][8]. The increased phospolipase A2 activity could potentially cause an increase in the levels of lysophospholipids which, if high enough, could be cytotoxic.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We have also demonstrated that differentiated HL-60 cells have about 2-3 times more lysophospholipase activity than do undifferentiated cells. The results shown in Table 1 are similar to results obtained by previous investigators [3][4][5][6][7][8]. The increased phospolipase A2 activity could potentially cause an increase in the levels of lysophospholipids which, if high enough, could be cytotoxic.…”
Section: Discussionsupporting
confidence: 89%
“…Differentiated HL-60 cells have increased capacity for the production ofa number ofproinflammatory mediators, including eicosanoids [4][5][6]. Phospholipase A2 activity has also been shown to increase upon differentiation of the HL-60 cells [7].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence was obtained that 15-hydroxyprostaglandin dehydrogenase (NAD+) (15-PGDH; EC 1.1.1.141) activity was downregulated in AML, due to the massively reduced plasma levels of 15-keto-PGE2, which was detected in only 1/20 AML plasma samples. HL-60 cells have been reported to possess this metabolic activity with respect to PGE2 and 15-HETE [44]. Both of these activities in vivo were observed in this study to be diminished in AML patients.…”
Section: Discussionsupporting
confidence: 67%
“…The latter would be the first reaction products, and, in the case of C18 PUFAs, would be also subject to oxidation to keto acids, a process which is not likely to occur non-enzymically because it cannot be observed with C20 PUFAs or DHA. No interconversion between 9-hydroxy and 9-keto acids was found in contrast to the situation described in mammalian tissues (Agins et al, 1987;Earles et al, 1991).…”
Section: Discussioncontrasting
confidence: 81%